The Effect of Social Media on Adolescents’ Sexual Behavior at SMA Negeri Unggul Binaan Bener Meriah in 2025 - Mauhizah Hasanah; Jumirah Jumirah; Ramadhani Syafitri Nasution (Universitas Ibn Khaldun Bogor, 2026)
The rapid development of technology has made social media an essential part of adolescents’ lives, not only as a means of communication but also as a platform for self-exploration and access to information, including sexual content. This study aims to analyze the influence of social media use on adolescents’ sexual behavior. This study employed a quantitative design with a cross-sectional approach. The population consisted of 320 adolescents, with a sample of 178 respondents selected using stratified random sampling based on the Slovin formula. Data were analyzed using univariate, bivariate, and multivariate methods. The results showed that there was a significant influence of social media usage intensity (p = 0.039), the role of teachers and parents (p = 0.014), and specific social media platforms such as Instagram, TikTok, and WhatsApp (p = 0.001) on adolescents’ sexual behavior. Meanwhile, knowledge (p = 0.258) and attitudes (p = 0.835) did not show a significant influence. The most dominant variable affecting adolescents’ sexual behavior was the role of social media, with TikTok being the most influential platform. In conclusion, social media use and the social environment play an important role in shaping adolescents’ sexual behavior. Therefore, increased supervision and education from teachers and parents are necessary, along with strengthening digital literacy and reproductive health programs in schools as efforts to prevent risky sexual behavior among adolescents.